50 Mathematical Ideas You Really Need to Know - Tony Crilly (India Hachette, 2022)
Just the mention of mathematics is enough to strike fear into the hearts of many, yet without it, the human race couldn't be where it is today. By exploring the subject through its 50 key insights - from the simple (the number one) and the subtle (the invention of zero) to the sophisticated (proving Fermat's last theorem) - this book shows how mathematics has changed the way we look at the world around us.
Keywords: TOK Collection -- TOK Collection